Cryopreservation Protocol Optimization for Penaeus monodon Sperm: Reagent Screening and Parameter Refinement - Dewei Kong; Song Jiang; Jianzhi Shi; Qibin Yang; Jianhua Huang; Yundong Li; Yangyang Ding; Jieyi Wang; Xinyu Qi; Tianmi Liu; Falin Zhou (Biology)
Penaeus monodon (black tiger shrimp) is one of the important shrimp species in aquaculture. Cryopreserving its sperm not only provides technical support for breeding but also effectively prevents the decline of genetic resources, promoting the sustainable development of its aquaculture industry. This study screened different types of diluents, cryoprotectants, and concentrations and explored equilibration time, cooling protocols, and thawing conditions, ultimately determining the optimal cryopreservation protocol for P. monodon sperm. The results showed that the optimal cryopreservation protocol involved using natural seawater as the diluent with 10% dimethyl sulfoxide (DMSO) as the cryoprotectant, in which the sperm suspension and cryoprotectant were mixed at a 1:1 (v/v) ratio and equilibrated at 4 °C for 30 min. Subsequently, cooling was performed using a programmable controlled-rate freezer: the temperature was reduced to −20 °C at −5 °C/min and held for 5 min; then cooled to −80 °C at −10 °C/min and held for 5 min; finally, the temperature was reduced to −180 °C at −20 °C/min. After cooling, the sperm samples were transferred to liquid nitrogen for long-term storage. The results demonstrated that thawing in a 37 °C water bath achieved the highest sperm motility compared to conditions at 27 °C, 32 °C, 42 °C, and 60 °C. After 15 days of liquid nitrogen storage, the sperm survival rate was 53.33 ± 9.18%. Scanning electron microscopy (SEM) and transmission electron microscopy (TEM) observations revealed that the sperm structure was intact before freezing, with a rounded head, a distinct acrosomal spike anterior to the head, a concentrated nucleus in the head, dense chromatin, and a smooth cell membrane surface. However, after freezing and thawing, the acrosomal spikes of some sperm were fractured, and the membrane structure was damaged. Enzyme activity analysis showed that during liquid nitrogen storage from 0 to 15 days, the enzyme activity of alkaline phosphatase (AKP) and acid phosphatase (ACP) in sperm gradually increased with significant differences observed compared to day 0 (p < 0.05). The activity of malondialdehyde (MDA) showed a gradual increase at 0, 5, and 10 days, but then decreased at day 15. The enzyme activity of catalase (CAT) showed no significant changes from 0 to 10 days (p > 0.05) but significantly increased on day 15 (p < 0.05). The activity of total superoxide dismutase (T-SOD) showed no significant changes from 0 to 5 days (p > 0.05) but significantly increased from days 10 to 15 (p < 0.05). These findings provide valuable insights into the cryopreservation of P. monodon sperm and will guide the optimization of cryoprotectant combinations and freezing protocols aimed at improving sperm survival rates.